After the Death of Charismatic Authority: A Weberian Perspective on Early Islam - MOHAMMAD SYIFA AMIN WIDIGDO (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2017)
In Max Weber’s notion of authority, charismatic authority will transform into other forms of either traditional authority, rational authority, or both. After the death of charismatic leader, in Weber’s word, charismatic authority is “fated to decline.” A number of studies on Weber and Islam seem to affirm Weber’s thesis regarding the decline of charismatic authority after the death of the charis-matic leader. However, in the context of early Islam, charismatic authority is not declining, even reinforced after the death of the charismatic leader, namely Prophet Muhammad. Therefore, this paper aims to show why charismatic authority after the death of charismatic leader is not waning in the early Islam and how such authority is even reinforced. By using Alasdair McIntyre’s theory of human vul-nerability, this paper investigates “material and ideal interests” of Muslims after the death of the Prophet, which make charisma of the prophet not declining, even more strengthened through invocations and venerations by his followers in subsequent generations. In this regard, the return of charismatic authority takes place not in the physical form of charismatic leader, but in the forms of images, sayings, and exemplary practices of the deceased charismatic leader, which are deemed worth emulating and invocation.